Pengembangan Video Tutorial Teknik Jahit Bulu Mata Pada Tata Rias Pengantin India - Tresna, Nazla Alinkaputri; Irtawidjajanti, Sri (Jurnal Tata Rias, 2023)
Making eyelash sewing tutorial videos for Indian brides includes Indian bridal makeup and eyelash sewing techniques. This study aims to make a product in the form of a proper video tutorial. Indian bridal makeup features a facial look that creates bold results. It has a characteristic in the eyebrows and eye makeup that makes the eyes look sharper. The eyelash sewing technique makes our eyes seem more open and rounder. The process in making this video consists of planning, production, and pos. This research is a research and development (R&D). The results of making this video meet the validation criteria are as follows: material experts rate it 80%, and media experts rate it 100%. It can be concluded that the video is a feasible alternative medium, making it easier to access information and knowledge related to eyelash sewing tutorial videos for Indian brides. t-production processes.